WAYS OF REALIZATION THE PRINCIPLE OF CONTINUITY IN THE ECOLOGICAL EDUCATION OF CHILDREN IN MODERN INSTITUTIONS OF PRESCHOOL EDUCATION AND ELEMENTARY SCHOOLS - Tamara Marchii-Dmytrash (Vasyl Stefanyk Precarpathian National University, 2018)
The essence of the concept "ecological culture" is determined in the article and it is substantiated that the basis of its forming in children of senior preschool age is the content of the program of studing and education in the preschool educational institutions, and in primary school children the content of the educational subject "Natural science" in the elementary school, through which the teacher acquaints children with the environment and forms in close cooperation with parents a thrifty attitude towards it. For this purpose, the teacher realizes the principle of continuity as interconnected content, methods, forms and means of ecological education in order to form an ecologically educated and cultural personality.It is determined the components of the ecological culture of preschool age children (the absorption of nature, the level of knowledge, abilities, skills to act in the nature, interest in the studing of nature, ecological consciousness, environmental activity) and the elementary school age children (knowledge about the interrelations in nature and the awareness of man as a part of it, assessment of people's behavior in nature, participation and organization in environmental activities, negative attitude to actions that are harmful to the natural environment). The pedagogical conditions of ecological education of senior preschool and junior school age children (the ecological orientation of educational work of educational establishments, usage of different kinds of activity, increase of the level of professional training of personnel, cooperation of educational establishments, schools, family, taking into account age, individual and psychological peculiarities of children of the senior preschool and junior school age, application of information of ecological content in practice) are substantiated.It is determined that content, methods, forms and means of ecological education used by the teachers of preschool institutions and primary schools  influence on forming the ecological culture of children of the senior preschool and junior school age. The place of games, works of fiction, modeling of ecological situations in forming of children's ecological culture is justified and the examples are given. It is emphasized on the necessity of cooperation between preschool and primary educational institutions with the family. Key words: ecological education, ecological culture, continuity principle, children of preschool age, primary school children, institution of preschool education, primary school.